The outcomes of surgical management of failed two-stage revision knee arthroplasty - Maden, Carla; Jaibaji, Monketh; Konan, Sujith; Zagra, Luigi; Borella, Matteo; Harvey, Adrian; Volpin, Andrea (Acta Biomedica Atenei Parmensis, 2021)
Background Joint infection following total knee arthroplasty has significant consequences on both the patient and healthcare system. Two stage revision arthroplasties is viewed as the gold standard in management. However, recurrence of infection following this procedure is a growing clinical problem for a multitude of reasons. Despite a variety of surgical options for management of failure of two-stage revision arthroplasty, the potential for complications and functional limitation remains high, and the optimal strategy is yet to be determined. Methods We performed a systematic review of all papers reporting on the outcomes of the surgical management of failure of two-stage revision arthroplasty published up to and including January 2020. Data was extracted on patient demographics, study design, methodological quality, indication for surgery, surgical technique, clinical and functional outcomes, and complications. Results Nine papers with a total of 273 patients were found and analysed All surgical techniques had mixed results in term of clinical and functional outcomes, and the rate of complications was high in all studies. Knee arthrodesis had the lower risk of failure than repeat 2 stage revision. Poor patient immunological status and limb status were weakly associated with increased risk of failure. Conclusion Despite failure of two-stage revision arthroplasty being a growing clinical issue, we were not able to identify any consistently superior surgical technique for the management of this scenario. Knee arthrodesis appears to provide the best results for improving quality of life and reducing infection recurrence, although the complication rate is high and the functional outcomes appear to be worse. Further larger and prospective studies are needed to elucidate optimal surgical management in different patient subsets.